KOMUNIKASI PERSUASIF ORANG TUA DALAM PENCEGAHAN KECANDUAN GADGET PADA ANAK - Ridwan Muhammad Hasan; Radifa Rahma Putri (Madrasa : Jurnal Ilmu Pendidikan dan Teknologi, 2025)
Persuasive Communication Techniques Used by Parents in Preventing Gadget Addiction in Children: A Study in Gampong Neusu Jaya, Baiturrahman District, Banda Aceh City. This study aims to determine how persuasive communication techniques are used by parents in preventing gadget addiction among children in Gampong Neusu Jaya and to identify various factors that influence the effectiveness of parental communication in preventing gadget addiction among children. This study is a qualitative study, with a descriptive research design, using observation, interviews, and documentation techniques. The research subjects consisted of 15 people, comprising 13 mothers and 2 fathers who had children aged 6-12 years. Based on the results of interviews with parents, the findings of this study are that in preventing gadget addiction in children, parents use persuasive communication techniques. The techniques used are open communication between children and parents, setting time limits on gadget use, providing alternatives by inviting children to do other activities, conveying messages to children about the negative effects of excessive gadget use, and communication between fathers and mothers. Factors influencing the effectiveness of parental communication in preventing gadget addiction in children include communication barriers between parents and gadget-addicted children, consistency in enforcing rules, parental discipline, and the initial use of gadgets by children based on educational needs, which eventually leads to a shift in the use of gadgets by children.